ANALISIS PENGENDALIAN KUALITAS PROSES PRODUKSI PIE SUSU PADA PERUSAHAAN PIE SUSU BARONG DI KOTA DENPASAR - Sari, Ni Kadek Ratna; Purnawati, Ni Ketut (E-Jurnal Manajemen; Vol 7 No 3 (2018), 2018)
The purpose of this study to determine whether the quality control performed by the Pie Susu Barong Company is optimal. The research was conducted at Pie Susu Barong Company in Denpasar City. This research uses descriptive research method. Sampling method using random sampling. The data used is the number of product damage in the period of October to November 2017. Data analysis techniques using statistical quality control tools, there are p control diagram, cause and effect diagram, and cost quality analysis. The result of quality cost analysis shows that quality control is not optimal yet, because the actual damage level of 7884 pie of milk total quality cost (TQC) is Rp 45,130,510 consisting of quality control (QCC) cost Rp 35.669.710 and quality assurance cost (QAC) amounting to Rp 9,460,800 is greater than the damage level of 15,308 milk pie seeds with total cost of optimum quality (TQC*) of Rp 36,740,386 consisting of quality control (QCC*) cost of Rp 18,370,786 and quality assurance cost (QAC*) of Rp 18,369,600. Keywords: Quality, Quality Control, Quality Cost, Statistical Quality Control